Examining Absorptive Capacity in the Adoption of Digital Health Technology in Indonesian Hospitals (a Theoretical Review and Implementation Perspective) - Teguh Setiawan Wibowo; Mochamad Fatchurrohman (LPPM STIE YAPAN, 2026)
This study aims to examine the concept of absorptive capacity and its relevance to the adoption of digital health technology in Indonesian hospitals. Through a literature review employing conceptual analysis and theoretical synthesis, this article traces the development connects it to the characteristics of healthcare organizations. The review indicates that the successful adoption of digital technology is not sufficiently achieved through the acquisition stage alone but demands sustained capabilities in assimilating, transforming, and exploiting knowledge. The analysis identifies four contextual factors influencing hospital absorptive capacity: organizational structure, professional culture, resources, and government regulation. This article offers a conceptual framework integrating three levels of analysis: individual, team, and organization with circular process dynamics that create either a virtuous cycle or a vicious cycle. Implementation implications include a shift from a project-based approach to a continuous process, reconfiguration of management roles, strengthening cross-professional collaboration, developing contextual measurement instruments, and establishing a supporting ecosystem at the macro level.